Produktivitas dan Serapan Nutrien Harian Spirogyra sp. dan Hydrodictyon sp. - Pratiwi, Niken Tunjung Murti; Ayu, Inna Puspa; Nugraha, Bayu (Perhimpunan Biologi Indonesia, 2016)
This research aimed to analyze the potency of primary productivity (PP) and daily nutrients uptake ofSpirogyra sp. and Hydrodictyon sp. The research was conducted using Randomized Block Design andCompletely Randomized Design. Randomized Block Design was used to determine the difference of PP ofboth filamentous microalgae in different time periods. Completely Randomized Design was used to determinethe difference of daily net primary productivity and total amount of nutrients utilization by both filamentousmicroalgae in the same light intensity. The observations showed that Spirogyra sp. dan Hydrodictyon sp. hassame PP (p>0,05), both in total (daily) and time periods. The morning PP of two filamentous microalgae weredifferent from the daylight (p<0,05), and the daylight has different value from the afternoon (p<0,05), but therewere similar value of PP between morning and afternoon (p>0,05). Spirogyra sp. and Hydrodictyon sp. hassimilar capability in uptaking nutrients daily and in time periods observations (p>0,05).Keywords: Hydrodictyon sp., nutrients, primary productivity, Spirogyra sp.